ChemInform Abstract: New Isosteroidal Alkaloids with Tracheal Relaxant Effect from the Bulbs of Fritillaria pallidiflora Schrenk. Issue 32 (July 2016) - Li, Yan; Yili, Abulimiti; Li, Jun; Muhamat, Aziz; Aisa, Haji Akber
Abstract: Four new isosteroidal alkaloids, yibeinone A (I), yibeinone B (II), yibeinones C (III), and yibeinone D (IV) are isolated from the bulbs of Fritillaria pallidiflora together with four known ones.